VIDEO MOVING SURVEILLANCE YANG TERINTEGRASI YOUTUBE MENGGUNAKAN RASPBERRY PI 3 - Utami, Pipit; Putra, Abdul Aziz Sidiq Tri; Santoso, Djoko; Fajaryati, Nuryake; Destiana, Bonita; Ismail, Mohd Erfy (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2018)
Static CCTV facilities in class need to be optimized in classroom learning, especially in recording learning activities as implementation of learning in the 21st century and strategic steps to face the Industrial Revolution 4.0. Educators need to play a role in utilizing CCTV in learning. This article presents the development of YouTube Integrated Video Moving Surveillance devices using Raspberry Pi 3. The development stages consist of analysis, design, development and evaluation. The analysis shows that: (1) the limitations of CCTV motion are followed up with the addition of motorcycles; (2) limited access to video recording data is followed up by sending in real time using YouTube; and (3) controlling the system performance of the device using Raspberry Pi 3 model B. The evaluation results show that all electronic measurement parameters are in accordance with the success target and the functional test shows that the device can function to record classroom learning activities that can be monitored in real time via YouTube with good quality (average delay is 22,89s). The results of the development of this device are expected to be an alternative use of technology in learning, especially in the supervision and assessment of student learning activities.